First European quality of life survey participation in civil society - Rose, Richard; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2006)
The term 'civil society' typically refers to organisations that mediate between the state and individuals. Political parties, trade unions, business associations, charitable bodies and cultural groups are all examples of civil society organisations. Informal social networks of friends, work colleagues or neighbours can also constitute the building blocks of formal organisations. While civil society organisations are independent of the state, their activities are often in the public interest. Such organisations can make collective representations to government about the direction of public policies, as well as interpreting these policies for their members. Thus, they have an important role to play in European society.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Electronic books